Involvement of Superoxide Dismutase in Spore Coat Assembly in Bacillus subtilis - Henriques, Adriano O. (American Society for Microbiology, 1998)
Endospores of Bacillus subtilis are enclosed in a proteinaceous coat which can be differentiated into a thick, striated outer layer and a thinner, lamellar inner layer. We found that the N-terminal sequence of a 25-kDa protein present in a preparation of spore coat proteins matched that of the Mn-dependent superoxide dismutase (SOD) encoded by the sodA locus. sodA is transcribed throughout the growth and sporulation of a wild-type strain and is responsible for the SOD activity detected in total cell extracts prepared from B. subtilis. Disruption of the sodA locus produced a mutant that lacked any detectable SOD activity during vegetative growth and sporulation. The sodA mutant was not impaired in the ability to form heat- or lysozyme-resistant spores. However, examination of the coat layers of sodA mutant spores revealed increased extractability of the tyrosine-rich outer coat protein CotG. We showed that this condition was not accompanied by augmented transcription of the cotG gene in sporulating cells of the sodA mutant. We conclude that SodA is required for the assembly of CotG into the insoluble matrix of the spore and suggest that CotG is covalently cross-linked into the insoluble matrix by an oxidative reaction dependent on SodA. Ultrastructural analysis revealed that the inner coat formed by a sodA mutant was incomplete. Moreover, the outer coat lacked the characteristic striated appearance of wild-type spores, a pattern that was accentuated in a cotG mutant. These observations suggest that the SodA-dependent formation of the insoluble matrix containing CotG is largely responsible for the striated appearance of this coat layer.